Temperature-sensitive mutants in herpes simplex virus type 1 ICP4 permissive for early gene expression. - DeLuca, N A (1984)
A large number of temperature-sensitive (ts) mutants of herpes simplex virus type 1 (HSV-1) in the gene encoding the immediate-early transcriptional regulatory protein, ICP4, have been isolated and characterized with respect to expression of the immediate-early, early, and late viral gene products. The hallmark of these mutants is the overproduction of immediate-early gene products and the underproduction of early and late gene products. The present study involves the preliminary genetic and molecular characterization of two unique regulatory mutants of HSV-1, ts48 and ts303. Genetically, both mutants exhibit inefficient complementation with eight ts mutants in complementation group 1-2, which defines the gene for ICP4, and marker rescue experiments place the mutations in both mutants in the 3' portion of the coding sequence for ICP4. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis of ts48- and ts303-infected cell polypeptides synthesized at the nonpermissive temperature demonstrates that immediate-early polypeptides ICP4 and ICP27 are overproduced, with the simultaneous production of early polypeptides ICP6, ICP8, gB, and others. Immediate-early polypeptides are resynthesized upon temperature shift-up early in infection; however, shift-up late in infection does not result in the resynthesis of immediate-early polypeptides. Late gene products are either absent or underrepresented under long-term labeling conditions. To examine the effects of the mutations in ts48, ts303, and other ICP4 mutants specifically on early gene expression, trans-induction experiments were performed in cells transfected with the gene for chloramphenicol acetyltransferase under early gene control (tk) and superinfected with KOS, tsB32, ts48, and ts303. Mutant tsB32 did not induce chloramphenicol acetyltransferase activity above the basal level; however, ts48 and ts303 induced chloramphenicol acetyltransferase activity nearly equal to wild-type levels. Fifteen to fifty percent of wild-type levels of viral DNA are synthesized at the nonpermissive temperature in ts48- and ts303-infected cells, indicating that immediate-early and early gene functions are intact (or nearly so) and that the block in ts48 and ts303 is in a regulatory event subsequent to that exhibited by other mutants in complementation group 1-2 which are DNA-.